Advantages of total parathyroidectomy in patients with secondary hyperparathyroidism induced by end stage renal disease - Iorga, Cristian; Iorga, Cristina Raluca; Andreiana, Iuliana; Bengulescu, Iustinian; Constantin, Traian; Strambu, Victor (Frontiers in Endocrinology, 2023)
Secondary hyperparathyroidism, as a result of chronic kidney disease could be treated medically or surgically. When pharmacotherapy fails, patients undergo surgery -parathyroidectomy, the curative treatment of secondary hyperparathyroidism (SHPT). There are currently 3 accepted surgical techniques, each with supporters or opponents - total parathyroidectomy, subtotal parathyroidectomy and parathyroidectomy with immediate autotransplantation. In this paper we described our experience on a series of 160 consecutive patients diagnosed with secondary hyperparathyroidism who underwent surgery, in 27 cases it was totalization of the intervention (patients with previously performed subtotal parathyroidectomy or with supernumerary glands and SHPT recurrence ). We routinely perform total parathyroidectomy, the method that we believe offers the best results. The group of patients was studied according to demographic criteria, paraclinical balance, clinical symptomatology, pre- and postoperative iPTH (intact parathormone) values, SHPT recurrence, number of reinterventions. In 31 cases we found gland ectopy and in 15 cases we discovered supernumerary parathyroids. A percentage of 96.24% of patients with total parathyroidectomy did not show recurrence After analyzsing the obtained results, our conclusion was that total parathyroidectomy is the intervention of choice for patients suffering from secondary hyperparathyroidism when pharmacotherapymedical treatment fails in order to prevent recurrence of the disease and to correct the metabolic parameters.